2019
DOI: 10.1080/25726641.2019.1684712
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the microstructures of iron ore sinters

Abstract: The phases and the phase assemblages present in selected industrial iron ore sinters have been analysed. A new experimental laboratory-based procedure has been developed that enables sintering experiments to be undertaken under controlled temperature and gas conditions. The results indicate that the formation of the complex silico ferrite of calcia and alumina phase (SFCA) phase is strongly influenced by the sinter bulk composition. Within the range of compositions of interest to industrial iron ore sintering,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…10) By analogy with the phase equilibria in the SFC system, 5) this is equivalent to the temperature for the peritectic reaction, H + L → SFCA + L. The critical temperature for decomposition of hematite and SFCA formation in samples containing 2wt%Al 2 O 3 in air have not been determined explicitly but SFCA has been observed in samples containing 1wt%Al 2 O 3 at 1 513 K (1 240°C) 10) and 2wt%Al 2 O 3 at 1 523 K (1 250°C). 4) It is therefore anticipated that, in the sample 88 wt% Fe 2 O 3 , 2 wt% Al 2 O 3v and CaO/SiO 2 = 3.5, SFCA will be present at 1 523 K (1 250°C).…”
Section: Formation Of Sfcamentioning
confidence: 99%
See 3 more Smart Citations
“…10) By analogy with the phase equilibria in the SFC system, 5) this is equivalent to the temperature for the peritectic reaction, H + L → SFCA + L. The critical temperature for decomposition of hematite and SFCA formation in samples containing 2wt%Al 2 O 3 in air have not been determined explicitly but SFCA has been observed in samples containing 1wt%Al 2 O 3 at 1 513 K (1 240°C) 10) and 2wt%Al 2 O 3 at 1 523 K (1 250°C). 4) It is therefore anticipated that, in the sample 88 wt% Fe 2 O 3 , 2 wt% Al 2 O 3v and CaO/SiO 2 = 3.5, SFCA will be present at 1 523 K (1 250°C).…”
Section: Formation Of Sfcamentioning
confidence: 99%
“…This common plane represents a potential nucleation site for SFCA minerals during the solidification process. It should be pointed out, however that magnetite has four (4) sets of close packed planes of oxygen within its crystal structure, represented by the < 111 > family of planes, (111), (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), and (-111). 30) This being the case it would be expected that the probability of nucleation of SFCA on magnetite crystal surfaces would be greater than on hematite.…”
Section: Sfca Nucleationmentioning
confidence: 99%
See 2 more Smart Citations
“…The industrial iron ore sinter product and return fine samples examined in the present study are the same as those reported in a previous study [27]. The bulk compositions of the sinter samples are adapted with permission from Ref.…”
Section: Overview Of Sample Informationmentioning
confidence: 99%